Effect of JAK Inhibitors on Fatigue and Sleep Quality in Patients with Rheumatoid Arthritis: A Narrative Review - Aleksandra Kowalska; Aleksandra Borkowska; Aleksandra Jawoszek; Grzegorz Chmielewski; Łukasz Jaśkiewicz; Magdalena Krajewska-Włodarczyk (Journal of Clinical Medicine, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disease in which fatigue and sleep disturbances, in addition to articular symptoms, are of significant importance. These symptoms are among the most common and burdensome complaints reported by patients; they affect their daily functioning and quality of life, and can also exacerbate one another. Currently, the treatment of RA focuses not only on reducing inflammatory activity and preventing structural damage, but also on improving outcomes that matter most to patients. In modern RA treatment, Janus kinase inhibitors (JAKis) are becoming increasingly important; by inhibiting the JAK/STAT pathway, they limit the activity of cytokines involved in the inflammatory response. This review aimed to analyse the effect of selected JAKis on fatigue and sleep quality in patients with RA. An analysis of available study results showed that baricitinib, filgotinib, tofacitinib and upadacitinib reduce fatigue severity. In many cases, improvement was observed as early as the initial stages of treatment and persisted at later follow-up points. At the same time, the extent of this improvement was not uniform and depended on the drug used, the dose, the patient population, and the assessment method adopted. Some analyses also suggested that this effect may have been partly due to reduced pain and improved disease activity. The data on sleep quality are less extensive, but the results suggest that tofacitinib and upadacitinib may also have a beneficial effect in this regard. With tofacitinib, improvements in sleep quality were observed early, affected multiple sleep domains, and, in some studies, persisted over the long term. For upadacitinib, an improvement in sleep quality appeared to be associated with disease control and remission. The smaller number of studies on sleep quality than on fatigue highlights the need to consider this parameter more thoroughly when assessing the efficacy of JAKi treatment and emphasises the importance of a more holistic approach in clinical practice.